Metal materials processes and manufacturing : selected, peer reviewed papers from the 2nd International conference on Metal material processes and manufacturing (ICMMPM 2019), July 30-31, 2019, Jeju Island, South Korea - Jung, Dong Won (Materials science forum ;, 2020)
The 2nd International Conference on Metal Material Processes and Manufacturing (ICMMPM 2019, July 30-31, 2019, Jeju Island, South Korea) reflects the main tendencies in the field of research and development of functional materials and metalworking technologies, solutions in special technologies and materials for the MEMS production, applied biotechnologies, waste recycling and computational materials science. Steel, Alloys, Metalworking, Grinding, Forming, Rolling, Electrical Discharge Machining, Abrasive Finishing, Cutting, Friction Stir Welding, Ceramics, Semiconductors, Nanocomposites, Thin Films, Coating, Corrosion, Polymers, Computational Materials Science, Waster Recycling, Absorption, Biotechnology, Laser Micro Milling, MEMS Materials Science, Mechanical Engineering, Bioscience and Medicine.